The Relationship between Blood Glucose Levels, Body Mass Index, and Physical Activity with the Incidence of Dermatophytosis among Patients at the Dermatology Clinic of RSUD Praya - Baiq Nedya Darari Arwa; Wiwin Mulianingsih; Dian Rahadianti; Rozikin Rozikin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Dermatophytosis is a superficial fungal infection affecting keratinized tissues, primarily driven by metabolic profiles and lifestyle choices. This study aimed to investigate the correlation between blood glucose concentrations, Body Mass Index (BMI), and physical activity levels with the prevalence of Dermatophytosis at the Dermatology Clinic of RSUD Praya. Employing an analytical observational approach with a cross-sectional framework, the research involved 84 subjects selected through consecutive sampling. Data were synthesized from medical records, structured interviews, BMI assessments, blood glucose screenings, and the International Physical Activity Questionnaire (IPAQ), followed by analysis using Chi-Square tests (α<0.05). The findings indicated a significantly higher frequency of Dermatophytosis among patients with hyperglycemia (p=0.004), overweight status (p=0.001), and high levels of physical exertion (p=0.001). In summary, blood glucose levels, BMI, and physical activity are key determinants significantly associated with the incidence of Dermatophytosis among patients at RSUD Praya.